Practice of Interfaith Marriages in Indonesia on Islamic Jurisprudence - Okti Nur Hidayah; Nurul Husnah; Wati, Felia; Salahuddin, Muhammad (International Journal of Social Science and Religion (IJSSR), 2023)
This article discusses Islamic jurisprudence in responding to the practice of interfaith marriages in Indonesia. The practice of interfaith marriages in Indonesia has occurred, despite rejection from various Islamic circles. According to Islamic law, in this case the Indonesian Ulema Council (MUI) has prohibited the practice of marriage. This interfaith marriage cannot achieve the true goal of marriage. This research uses a normative approach using the Sadd Dzari'ah theory. Sadd Adzariah refers to actions that initially provide benefits, but end in losses. The conclusion of this research shows that the Sadd Dzari'ah concept in prohibiting interfaith marriages aims to prevent religious change and avoid potential conflicts within the family. Interfaith marriages can cause one of the Muslim partners to change their faith, so the clerics prohibit it to prevent negative impacts such as changing beliefs. In addition, restrictions on interfaith marriages aim to create peace in the family and prevent children who marry non-Muslims from following non-Muslim religions. This prohibition also aims to avoid divisions in the family.